Synthesis of metal organic framework (MOF-5) embedded cryogel composite and its application for the extraction and determination of cholesterol from milk samples - Chang, Fouzia; Memon, Najma; Shaikh, Huma; Memon, Ayaz Ali; Memon, Shahabuddin; Memon, Paras Aazadi; Chang, Abdul Sattar (European Journal of Chemistry, 2021)
Metal-organic frameworks (MOFs)/coordination polymers (CPs) are a new class of hybrid inorganic/organic porous material. Recently MOFs have attracted much attention due to their large surface area, tunable pore structure, and high thermal stability. MOF-5 is composed of zinc salt and 1,4 benzene dicarboxylic linker. In the current study, MOF-5/cryogel composite was applied to extract cholesterol selectively from milk samples. This extraction process was used to clean-up milk samples with MOF-5/cryogel composite followed by determination of cholesterol in milk using UV-Vis spectrophotometric technique. The parameters such as concentration of cholesterol, volume of cholesterol solution, adsorbent amount, adsorption and desorption time were studied to obtain good extraction of cholesterol. The amount of cholesterol adsorbed and desorbed was 84 and 80%, respectively, from milk samples using MOF-5 composite cryogel. The developed method was validated in terms of linearity, accuracy, precision, limit of detection, and quantification. The response was linear in the range of 5-200 µg/mL with a coefficient of determination (r2) of 0.990. Detection limit (0.15 µg/mL) and quantification (0.45 µg/mL) were obtained.